Condom use in young women using long-acting reversible contraception (LARC): a qualitative study. Issue 8 (9th August 2021) - Murphy, Nabreesa; Williams, Henrietta; Nguyen, Julie; McNamee, Kathleen; Coombe, Jacqueline; Hocking, Jane; Vaisey, Alaina
Abstract: Young women in Australia disproportionately experience unintended pregnancy and sexually transmissible infections (STIs). As the promotion of highly effective pregnancy prevention methods such as long-acting reversible contraception (LARC) increases, concurrent use of condoms with LARC remains optimal for pregnancy and STI prevention. There is little data exploring condom use behaviour in young Australian women using LARC. In this qualitative study we interviewed twenty women using LARC about their experiences of making decisions regarding condom use. We used inductive thematic analysis to identify factors influencing participant decision-making. We found that while LARC had an impact on condom use and sexual practices, decisions regarding condom use were influenced by multiple factors including mood, menstrual changes related to LARC, and relationship dynamics. Participants' views of 'safe sex' extended beyond pregnancy and STI protection, to include desired outcomes such as pleasure, consent and communication. Access to STI testing and treatment was key to how participants managed STI risk. Findings highlight the need for a more comprehensive approach to safer sex health promotion, and the importance of ensuring STI testing and treatment services continue to be available and accessible to all young people.